Supporting Process of Independent Navigation Inside Buildings Based on Low-Energy Bluetooth Transmitters - Żochowski, Tomasz (Studia Informatica. System and information technology, 2021)
Thanks to the use of satellite positioning systems (including GPS) the ability to determine a user’s position in open spaces has become a necessary element of everyday life. Nowadays people cannot imagine moving in an "urban jungle” with paper maps without electronic support, but dozens of years ago those maps were more popular than satellite navigation. A similar revolution may also await navigations in closed spaces such as public or commercial buildings. Because as the urbanisation process, the surfaces of various buildings grow, which significantly impedes orientation in them, especially for the blind or visually impaired users. As satellite navigation systems are burdened with errors, which increase when trying to use them in confined spaces, it becomes necessary to use more accurate technology. As a step towards solving this problem, we propose a solution supporting the navigation of users, especially the visually impaired, inside buildings. Our approach is based on using low energy Bluetooth transmitters and a method of determining the user’s position using the trilateration algorithm and the appropriate placement of transmitters in a space.